Technology-Mediated Strategies for Managing Writing Anxiety across Extrovert and Introvert EFL Students - Indri Wirahmi Bay; Nonny Basalama; Sartin Miolo; Rahman Taufiqrianto Dako (Language, Technology, and Social Media, 2026)
Writing anxiety remains a persistent challenge for EFL university students, shaping their cognitive, affective, and behavioral engagement with academic writing. While digital and AI-assisted tools are increasingly used to support writing development, little is known about how learners with different personality traits particularly extroverts and introverts employ technology to manage writing-related anxiety. This article reports the qualitative component of an explanatory sequential mixed-methods study that examined levels, types, causes, and coping strategies of English writing anxiety among Indonesian EFL undergraduates. Building on quantitative findings derived from the EPQ, SLWAI, and CWAI, semi-structured interviews were conducted with 20 purposefully selected students (10 extroverts; 10 introverts) to explore their technology-mediated coping strategies. Thematic analysis revealed clear personality-based distinctions. Extrovert students relied on stimulation-rich, interactive, and feedback-oriented technologies including YouTube tutorials, social media videos, writing applications, and AI tools to boost motivation, model writing processes, and reduce fear of errors. Technology served as an external scaffold that energized their writing engagement. In contrast, introvert students preferred quiet, private, and self-paced digital environments. They used calming media, reference-based tutorials, translation tools, vocabulary apps, and AI feedback to regulate emotions, clarify ideas, and resolve linguistic uncertainties in low-pressure settings. Technology functioned as an internal regulator that supported cognitive clarity and emotional steadiness. These findings underscore that technology-mediated coping is personality-sensitive, highlighting the need for flexible, personalized digital interventions to support diverse emotional and cognitive needs in EFL writing contexts.